Colored nanoparticles for ecological dyeing of cellulosic fibers - Gomes, Jaime Rocha (2011)
Dyeing cellulosic fibres with reactive dyes wastes great quantities of salt and water. The objective of this work is to dye cellulosic fibers using colored nanoparticles (CNPs) as an alternative to dyeing with reactive dyes. CNPs do not need salt nor soaping after dyeing, consuming less than 50% of water.